Pengaruh Model Pembelajaran Inkuiri Terbimbing terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Peserta Didik - Waleulu, Amalia; Muharram, Muharram; Sugiarti, Sugiarti (Chemistry Education Review (CER), 2019)
The research aims to examining the influence of guided inquiry learning model on critical thinking ability and chemistry learning autcomes of students on chemistry bond learning material. This research method uses an experimental method with two treatments. Data analysis using normality test, homogeneity test, hypothesis test and analysis to test the hypothesis was using one way ANOVA at a significant level of 0.05. The ruselt of descriptive analysis obtained the mean score of critical thinking ability and learning outcome in experiment class by 79.85 and the control class 57.89 whit each of standard of deviation 11.77 and 12.29. The mean percentage of critical thinking ability indicator in experiment class is 83.91 in high category and in control class is 49.63 in moderate category. The result of hypothesis test with t-test at the level of significance α = 0.05 obtained tcount 4.48 > ttable 2.02 and significance (0.001 < 0.05) indicated that the hypothesis is accepted. The conclusion of the study is there influence of guided inquiry learning model on the critical thinking ability and learning outcomes of grade X MIA at SMA Muhammadiyah Luhu on Chemistry Bond learning material.